Evaluation of complication during third stage of labour at tertiary care center - Rangholiya, Komal K.; Agrawal, Saumya P.; Shah, Sapana R.; Dodiya, Hetal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of the present study was to determine the maternal outcome of complications of third stage of labour and to determine the risk factors and evaluate the management protocols for these complications. Methods: This is retrospective study of maternal outcome with complications of third stage of labour carried out at tertiary care centre from June 2016 to December 2019. Patients who developed any complications of third stage of labour after vaginal delivery or caesarean section were included. Results: Complications observed during third stage of labour were atonic PPH 0.82% (74 cases), traumatic PPH 0.55% (50 cases), retained placenta (including placenta accreta spectrum) 0.21% (19 cases), secondary PPH 0.03% (3 cases), uterine inversion 0.03% (3 cases) and amniotic fluid embolism 0.01% (1 case). Maximum cases were seen in 18-24 years of age group. Only 36% patients having atonic PPH responded to medical treatment, 46% patients having atonic PPH responded to conservative surgery, 18% of patients required radical surgery. Conclusions: Third stage complications are potentially life threatening. Associated conditions for third stage complication are high parity, anemia, hydramnios, multiple pregnancy, malpresentation, placenta previa, and adherent placenta. Early anticipation and early intervention with proper planning is required to reduce the maternal morbidity and mortality in third stage complication.